Humanitarian–development nexus approach to health systems strengthening in Sudan—a policy analysis - Aweesha, Huzeifa Jabir Idris; Hurtig, Anna-Karin; Pulkki-Brännström, Anni-Maria; San Sebastián, Miguel (Frontiers in Public Health, 2025)
BackgroundWith increasing conflict, fragility, and emergencies in many countries, health systems are being frequently weakened and require support and strengthening. To ensure the provision of lifesaving interventions while improving national health systems, the humanitarian–development nexus presents a policy solution to bridge the divide between humanitarian and development actors. Sudan represents an interesting case of the nexus of adoption in the context of protracted emergencies, a volatile political scene, and complex economic and partnership dynamics. This study aimed to explore the understanding and adoption process of the nexus approach to health systems strengthening in Sudan.MethodsWe conducted a policy analysis based on seven qualitative interviews conducted in 2022 with informants from varying humanitarian and development entities.ResultsOur findings revealed uncertainty surrounding the meaning and practicalities of the nexus, despite a consensus on its importance. At the same time, the introduction process was driven by global partners, the Government of Sudan’s adoption of the nexus, and the presence of relevant coordination mechanisms within the health sector, which facilitated the advancement of the nexus. However, the humanitarian and development actors expressed conflicting values and disagreements about the use of the financial management, procurement, and information components of the national health system.ConclusionSudan’s health partners have implemented various nexus-based practices to strengthen national health system capacities. However, the nexus approach has faced challenges due to conceptual ambiguities and inconsistent implementation. We call for the advancement of guidance and dialog on the approach, emphasizing the importance of ownership, coordination, and flexibility, with the belief that the humanitarian–development divide can be further bridged.